Impact of local and systemic factors on the incidence of failures up to abutment connection with modified surface oral implants - Ghada Alsaadi, Marc Quirynen, (Blackwell Synergy, 2008)
Aim: This study aimed to assess the influence of systemic and local bone and intra-oral factors on the occurrence of early TiUnitet implant failures. Material and Methods: A total of 283 consecutive patients (187 females; mean age 56.2), who received a total of 720 TiUnitet implants, at the Department of Periodontology of the University Hospital of the Catholic University of Leuven, were prospectively followed. The following aspects were particularly assessed: hypertension, cardiac problems, gastric problems, osteoporosis, hypo- or hyperthyroid, hypercholesterolaemia, asthma, diabetes types I or II, Crohn’s disease, rheumatoid arthritis, chemotherapy, hysterectomy and intake of medication (antidepressants, steroids, hormone replacement), radiotherapy of the concerned area, breach of sterility during surgery, implant parameters, bone (quality, quantity, dehiscence or perforation), type of edentulism, antibiotics prescription, fenestration of the implant in the sinus/nasal cavity, immediate implant placement, apical lesion detection and insertion torque. Results and Conclusion: A global failure rate of 1.9% was recorded. Owing to the very few failures, no definitive conclusion concerning statistical significance can be achieved. However, a tendency for more failures was noticed for apical lesions, vicinity with natural dentition, smoking, hormone replacement, gastric problems, Crohn’s disease, diabetes I and radical hysterectomy.